“Untethered”: How the majority decision in Toronto (City) v Ontario tries (but fails) to break away from the Supreme Court of Canada’s unwritten constitutional principle jurisprudence - Kazmierski, Vincent (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2022)
The majority reasons in the Supreme Court of Canada’s decision in Toronto (City) v Ontario appear to suggest that unwritten constitutional principles may not be applied as “independent” means to invalidate legislation. Indeed, some may argue that the majority reasons identify additional, categorical limitations on the application of unwritten constitutional principles. This article argues that that these categorical claims are not supported by the existing jurisprudence.In particular, the article argues that the categorical claims in the majority reasons in Toronto (City) are based on misinterpretations of the existing jurisprudence that, in turn, promote misconceptions about the ways unwritten constitutional principles may be recognized and applied. When these misinterpretations and misconceptions are identified, and dispelled, it is possible to see that the decision in Toronto (City) may be best understood as a response to the use of unwritten constitutional principles to protect overly broad rights claims, rather than a more general, categorical restriction of their normative power. It also becomes apparent that the question of whether unwritten constitutional principles may serve as “independent” limitations on legislation may be misplaced and that an approach based on categorical acceptance or rejection of particular roles for unwritten principles should be eschewed in favour of a more balanced, “sliding-scale” approach to the application of these principles, that weighs different categories of evidence in favour (or against) the application of a particular principle to support a new constitutional right or obligation. Such a sliding scale approach fits well within the Court’s existing jurisprudence.